(untitled) (Update Dental College Journal, 2019)
Introduction: The use of all types of smokeless tobacco poses a serious risk to the health of community members. The present study was conducted to classify the guild merchants using smokeless tobacco in Chabahar, Iran, based on the Trans-Theoretical Model (TTM) and then analyze the relationships between the examined variables based on the constructs of this model. Materials and Methods: This descriptive cross-sectional study was conducted on 320 merchants working in different guilds in Chabahar in 2018, who were selected through simple random sampling. The data collection tool was a researcher-made questionnaire with a demographic and background information section, behavioral items and items on the constructs of the transtheoretical model, and was used after its validity and reliability were confirmed. Data were analyzed in SPSS software using statistical tests such as mean and SD, the Chi-square test, the ANOVA and Tukey’s test. Findings: Most of the participants in the study were in the age group of 20-30 years (69%). Hairdressers and textile stores (19%) were the largest and hotel and restaurant businesses (2%) the smallest trade guilds in this study. Most people in the study consumed Gutkha (24%). A total of 85% of the subjects were in the precontemplation stage, 12.5% in the contemplation stage and 2.5% in the preparation stage, and the stages of change had a significant difference with constructs including counter-conditioning, self-liberation, decisional balance and temptation to use tobacco (P<0.05). Conclusion: Since most merchants were in the precontemplation stage, and given their age and the proven harms of smokeless tobacco, interventions to encourage these people to quit tobacco consumption using the TTM constructs are necessary. Update Dent. Coll. j: 2019; 9 (1): 16-22